Multicentre study of the impact of morbidity on long‐term survival following hepatectomy for intrahepatic cholangiocarcinoma. Issue 13 (15th September 2016) - Doussot, A.; Lim, C.; Gómez‐Gavara, C.; Fuks, D.; Farges, O.; Regimbeau, J. M.; Azoulay, D.; ,
Abstract : Background: The impact of morbidity on long‐term outcomes following liver resection for intrahepatic cholangiocarcinoma is currently unclear. Methods: This was a retrospective analysis of all consecutive patients who underwent liver resection for intrahepatic cholangiocarcinoma with curative intent in 24 university hospitals between 1989 and 2009. Severe morbidity was defined as any complication of Dindo–Clavien grade III or IV. Patients with severe morbidity were compared with those without in terms of demographics, pathology, management, morbidity, overall survival, disease‐free survival and time to recurrence. Independent predictors of severe morbidity were identified by multivariable analysis. Results: A total of 522 patients were enrolled. Severe morbidity occurred in 113 patients (21·6 per cent) and was an independent predictor of overall survival (hazard ratio 1·64, 95 per cent c.i. 1·21 to 2·23), as were age at resection, multifocal disease, positive lymph node status and R0 resection margin. Severe morbidity did not emerge as an independent predictor of disease‐free survival. Independent predictors of time to recurrence included severe morbidity, tumour size, multifocal disease, vascular invasion and R0 resection margin. Major hepatectomy and intraoperative transfusion were independent predictors of severe morbidity. Conclusion: Severe morbidity adversely affects overall survival following liver resection for intrahepatic cholangiocarcinoma. Abstract : Morbidity affects overall survival